2004
DOI: 10.1051/0004-6361:20041154
|View full text |Cite
|
Sign up to set email alerts
|

XMM-Newtonobservations of the supernova remnant RX J1713.7–3946 and its central source

Abstract: Abstract. We present new results from the observations of the supernova remnant (SNR) RX J1713.7-3946 (also G347.3-0.5) performed in five distinct pointings with the EPIC instrument on board the satellite XMM-Newton. RX J1713.7-3946 is a shelltype SNR dominated by synchrotron radiation in the X-rays. Its emission (emission measure and photon index) as well as the absorption along the line-of-sight has been characterized over the entire SNR. The X-ray mapping of the absorbing column density has revealed strong … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
180
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 153 publications
(199 citation statements)
references
References 47 publications
17
180
2
Order By: Relevance
“…It is surprising that RCW 86, where part of the shock emits thermal X-rays that trace ambient medium densities of ∼0.5 cm −3 , shows a similar HE spectral index to RX J1713.7−3946 where no thermal X-ray emission has been detected so far and where the density upper limit is very constraining (<0.02 cm −3 , Cassam-Chenaï et al 2004). Because of the density difference, we could have expected a higher fraction of hadronic emission in RCW 86 and thus a steeper spectral index at HE.…”
Section: Source Class Comparison At He and Vhementioning
confidence: 97%
“…It is surprising that RCW 86, where part of the shock emits thermal X-rays that trace ambient medium densities of ∼0.5 cm −3 , shows a similar HE spectral index to RX J1713.7−3946 where no thermal X-ray emission has been detected so far and where the density upper limit is very constraining (<0.02 cm −3 , Cassam-Chenaï et al 2004). Because of the density difference, we could have expected a higher fraction of hadronic emission in RCW 86 and thus a steeper spectral index at HE.…”
Section: Source Class Comparison At He and Vhementioning
confidence: 97%
“…The CO data 22 suggest that a cloud is interacting with the northwestern part of the SNR, where a striking spatial coincidence between the CO density peaks and the regions of peak X-ray emission is seen. The X-ray data 23 also indicate significant absorption column densities in the western part of the remnant, at values about twice those to the east. These indications fit qualitatively with the γ-ray image presented here, where TeV emission is seen from the whole SNR shell but with an increased flux from the northwestern side.…”
mentioning
confidence: 87%
“…Given the recent estimates [22][23][24] of the distance to the source of 1 kpc, if a significant part of the TeV flux were to be formed by interactions of cosmic-ray nuclei with gas atoms in the cloud with density n exceeding 100 cm −3 , the energetics implied by the γ-ray flux and the spectrum would be a few times 10 49 n −1 erg between 10 and 100 TeV. This is consistent with the picture of an SNR origin of Galactic cosmic rays involving about 10% efficiency for conversion of the mechanical energy of the explosion into non-thermal particles, and a production spectrum in the SNR which is approximately an E −2 power law from several GeV to about one PeV.…”
mentioning
confidence: 99%
“…Subsequent studies of this SNR with the ASCA satellite by Koyama et al (1997) and Slane et al (1999), and later with XMM by Cassam-Chenaï et al (2004), have not positively identified any thermal X-ray emission so they tentatively concluded that the observable X-ray emission is entirely nonthermal.…”
Section: Introductionmentioning
confidence: 93%